Treatment of Patients with Stable Manifestations of Atherosclerosis: New Opportunities - article Editorial (Рациональная фармакотерапия в кардиологии)
Conclusion of the Expert Panel (November 24, 2018)*Novosibirsk, 11/24/2018*The Composition of the Board of Experts: Novosibirsk: Lifshits G.I., Ekaterinburg: Burleva E.P., Grachev V.G., Lipchenko A.A., Khabarovsk: Davidovich I.M., Barnaul: Efremushkina A.A., Korennova O.Yu., Moscow: Karpov Y.A.** (Chairman), Vladivostok: Nevzorova V.А., Kemerovo: Barbarash OL, Krasnoyarsk: Petrova MM, Irkutsk: Protasov K.V., Tyumen: Shalaev S.V. The publication of the opinion was prepared with the support of the medical advisor of JSC BAYER Elovoy-Vronskiy A.A.. The resolution discusses the issues of diagnosis and management of patients with coronary artery disease depending on regional particularities, the role of the new approach to antithrombotic therapy of stable patients with atherosclerotic diseases and its pathogenetic basis (inhibition of both coagulation and platelet). Experts noted that combination of rivaroxaban 2.5 mg BID and acetylsalicylic acid can be recommended after registration of the indication for almost all patients with atherosclerotic diseases. Nevertheless, first of all this therapy, at any stage of patient management, should be considered for patients with high cardiovascular risk, namely, patients with multiple atherosclerotic lesions, patients with history of myocardial infarction after the termination of the period of double antiplatelet therapy and patients with concomitant diabetes mellitus, chronic kidney disease and other risk factors that worsen the prognosis. The experts expressed hope that soon the combined antithrombotic therapy will not only be registered for use in Russia but will also be included in the national guidelines for the management of patients with coronary artery disease or peripheral arterial disease.